Developing PISA-like Numerical Problem Using Vaccine Context During Pandemic - Ayu Luviyanti Tanjung; Zulkardi Zulkardi; Ratu Ilma Indra Putri (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2022)
This is a type of development research with the main stages of preliminary and formative evaluation consisting of self-evaluation, expert review, one-on-one, small group, and field tests, with the goal of producing valid and practical PISA-like numerical problems and having an effect potential in the context of vaccines during the COVID-19 pandemic. The participants in this study were eighth-grade students younger than 15 years old. The qualitative analysis of this study's findings was conducted on the basis of student responses to the field test. This study's data collection methods included walkthroughs, observations, interviews, and tests. This study produced the development of a PISA-like numerical problem with the characteristics of the Change and Relationship content, the vaccine context, and the social analysis context, all of which were valid and applicable. According to the results of the validator's evaluation, the questions are sound in terms of content, structure, and language. Practically illustrated from the results of small group trials where the majority of students can easily comprehend and interpret the material. Based on the results of field trials, it can be concluded that the PISA-like numerical problems in the context of a pandemic vaccine has the potential to improve students' mathematical literacy skills.